2019
DOI: 10.1136/bmjopen-2019-031220
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and adiposity in overweight and obese children and adolescents: a systematic review with network meta-analysis of randomised trials

Abstract: ObjectivesDetermine both the effects and hierarchy of effectiveness for exercise interventions (aerobic, strength training or both) on selected measures of adiposity (body mass index (BMI) in kg/m2, fat mass and per cent body fat) in overweight and obese children and adolescents.DesignNetwork meta-analysis of randomised exercise intervention trials.SettingAny setting where a randomised trial could be conducted.ParticipantsOverweight and obese male and/or female children and adolescents 2–18 years of age.Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 108 publications
(668 reference statements)
8
29
0
1
Order By: Relevance
“…It is well established that body fat is a strong risk factor for obesity-related comorbidities in youth [36]. Several studies have reported the beneficial effects of exercise alone for clinically relevant improvements in body composition and metabolic parameters in youth with obesity [4,5], because fat is a key factor in metabolic complications [36]. The present meta-regression analysis also indicates a negative relationship between CRF and change in percent body fat.…”
Section: Discussionsupporting
confidence: 62%
“…It is well established that body fat is a strong risk factor for obesity-related comorbidities in youth [36]. Several studies have reported the beneficial effects of exercise alone for clinically relevant improvements in body composition and metabolic parameters in youth with obesity [4,5], because fat is a key factor in metabolic complications [36]. The present meta-regression analysis also indicates a negative relationship between CRF and change in percent body fat.…”
Section: Discussionsupporting
confidence: 62%
“…Children with obesity generally report lower moderate-to-vigorous physical activity (MVPA) [ 120 ] and greater time spent in sedentary behaviors [ 121 ], which have been associated with greater adiposity measures [ 122 ]. As several randomized controlled trials (RCTs) investigating the effects of exercise on %BF, FM, or AT in healthy children across weight status have been published to date, pooled analyses of their findings were made possible through meta-analyses [ 123 , 124 , 125 ]. For example, García-Hermoso et al reported an effect of a supervised exercise intervention on reducing body fat in children with either healthy weight or overweight/obese, independent of mode and intensity [ 123 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…It is noteworthy, however, that most of the included studies have combined exercise with additional interventions (i.e., dietary counseling and environmental changes), concealing the direct effect of exercise on adiposity measures. Another recent meta-analysis including RCTs of exercise-only interventions with a duration ≥4 weeks in children with overweight or obesity compared the effects of exercise mode on FM and %BF [ 124 ]. Pooled data analysis revealed that combining aerobic and strength exercises resulted in the greatest reductions of adiposity measures, although aerobic exercise alone also reduced adiposity compared to control arms.…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…Regarding these physical exercise or psychomotor interventions, and according to the recent review of Kelley, et al [ 8 ], they should be the most important type of intervention for the overall physiological health of this group of age, given their clinically relevant improvements in adiposity outcomes, lack of adverse events and significant enhancements in a wide number of secondary outcomes. Regular exercise, especially aerobic training, is associated with the reduction of fasting insulin and HOMA-IR (homeostatic model assessment—insulin resistance) in children and adolescents with obesity and overweight [ 9 ].…”
Section: Introductionmentioning
confidence: 99%